Characterization of nanofillers - reinforced polymeric composite products fabricated by selective laser sintering - Melle, Zhongtao (2017)
Being one of the newest Additive Manufacturing methods in the modern industry, Selective Laser Sintering is capable using a wide range of materials to print objects with extreme complex shapes. However, there are still large numbers of undiscovered characteristics in both available printing materials and the process factors involved in this method. Various tests such as tensile test and compression test had been carried out by the author to determine the mechanical properties of the samples produced from the Polyamide 12-Carbon Nanotube, 1 wt% composite (PA12-CNTs, 1 wt%).